Top quark mass measurement using the template method in the lepton+jets channel at CDF II - Abulencia, A; Acosta, D; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; et al. (2006)
This article presents a measurement of the top quark mass using the CDF II detector at Fermilab. Colliding beams of protons and antiprotons at Fermilab's Tevatron (s=1.96TeV) produce top/antitop pairs, which decay to W+W-bb̄; events are selected where one W decays to hadrons and the other W decays to either e or μ plus a neutrino. The data sample corresponds to an integrated luminosity of approximately 318pb-1. A total of 165 tt̄ events are separated into four subsamples based on jet transverse energy thresholds and the number of b jets identified by reconstructing a displaced vertex. In each event, the reconstructed top quark invariant mass is determined by minimizing a χ2 for the overconstrained kinematic system. At the same time, the mass of the hadronically decaying W boson is measured in the same event sample. The observed W boson mass provides an in situ improvement in the determination of the hadronic jet energy scale. A simultaneous likelihood fit of the reconstructed top quark masses and the W boson invariant masses in the data sample to distributions from simulated signal and background events gives a top quark mass of 173.5-3.8+3.9GeV/c2. © 2006 The American Physical Society.